GE_GERICHTE P/22314/2020 vom 23. November 2021 - GE Cour de justice (2021)
DROIT D'ÊTRE ENTENDU;SÉQUESTRE(LP);CONFISCATION(DROIT PÉNAL);CRÉANCE;SOUPÇON;COMMERCE DE STUPÉFIANTS | CPP.3.al2.letc; Cst.29; CPP.197; CPP.263.al1.letd